2016
DOI: 10.1590/0001-3765201620150162
|View full text |Cite
|
Sign up to set email alerts
|

Tidal and sub-tidal sea level variability at the northern shelf of the Brazilian Northeast Region

Abstract: A characterization of the sea level variability at tidal and sub-tidal frequencies at the northern shore of the Brazilian Northeast shelf for the period 2009-2011 is presented. The sea level data used was obtained from the Permanent Geodetic Tide Network from the Brazilian Institute of Geography and Statistics for the Fortaleza gauge station. Local wind data was also used to assess its effects on the low-frequency sea level variability. The variability of the sea level was investigated by classical harmonic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…When applying the Mann-Kendall test, no statistically significant trend (Tau = -0.123; p= 0.16147) was observed in the dataset.The astronomical tide is the result of the interaction of the gravitational forces of Earth, Moon and the Sun, being completely predictable. With the DHN data set provided by the Brazilian Navy, it was observed that the maximum annual astronomical tide quota presented an average of 2.80 m and a 13 cm amplitude, with a maximum of 2.84 m and a minimum of 2.71 m. In the same study, when the Mann-Kendall test was applied, no statistically significant trend was observed (Tau = 0; p= 1),showing a steady pattern.The descriptive values on the tides presented to corroborate the values found in the literature Frota et al (2016),. studying the tidal behavior in the Brazilian Northeast during the period from 2009 to 2011 in buoys about 200 km from the Piranhas-Açú estuary, found that the average maximum tide height was 2.79 m, ranging from 2.23 at 3.34 m. In the same study, Frota et al(2016) found that the sea level variability in the sub-FT (The non-astronomical sea level signal) represents low oscillation, with a maximum of 0.12 m. Mattos et al (2019), conducted a campaign from December 2010 to February 2011 to study significant wave heights, found that the tide table of Guamaré-RN (approximately 40km East of the table of Macau-RN) had averages of 2.34 m (in syzygy tides) and 2.21 m (in quadrature tides), both above the reduction level.…”
supporting
confidence: 87%
“…When applying the Mann-Kendall test, no statistically significant trend (Tau = -0.123; p= 0.16147) was observed in the dataset.The astronomical tide is the result of the interaction of the gravitational forces of Earth, Moon and the Sun, being completely predictable. With the DHN data set provided by the Brazilian Navy, it was observed that the maximum annual astronomical tide quota presented an average of 2.80 m and a 13 cm amplitude, with a maximum of 2.84 m and a minimum of 2.71 m. In the same study, when the Mann-Kendall test was applied, no statistically significant trend was observed (Tau = 0; p= 1),showing a steady pattern.The descriptive values on the tides presented to corroborate the values found in the literature Frota et al (2016),. studying the tidal behavior in the Brazilian Northeast during the period from 2009 to 2011 in buoys about 200 km from the Piranhas-Açú estuary, found that the average maximum tide height was 2.79 m, ranging from 2.23 at 3.34 m. In the same study, Frota et al(2016) found that the sea level variability in the sub-FT (The non-astronomical sea level signal) represents low oscillation, with a maximum of 0.12 m. Mattos et al (2019), conducted a campaign from December 2010 to February 2011 to study significant wave heights, found that the tide table of Guamaré-RN (approximately 40km East of the table of Macau-RN) had averages of 2.34 m (in syzygy tides) and 2.21 m (in quadrature tides), both above the reduction level.…”
supporting
confidence: 87%
“…Also, the populations of L. leptodactyla could be clustered in three groups, corresponding to significant differences in carapace shape along a macrogeographic scale. Brazilian estuarine systems have a high variability of abiotic conditions (e.g., salinity, temperature, tidal regimes), with higher tidal regimes and mean temperatures in the north and northeast coast, that may account for the local morphological divergence and phenotypic plasticity (Frota et al., 2016). Nevertheless, an overlap of morphotypes with no clear pattern could still be observed (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…The descriptive values of the tides are presented to corroborate the values found in the literature. Frota et al (2016), studying the tidal behaviour in the Brazilian northeast during the period from 2009 to 2011 with buoys about 200 km from the Piranhas-Açu estuary, found that the average maximum tide height was 2.79 m, ranging from 2.23 to 3.34 m. In the same study, Frota et al (2016) found that the sea level variability in the sub-FT (the non-astronomical sea level signal) represents low oscillation, with a maximum of 0.12 m. Matos et al (2019) made a scientific expedition from December 2010 to February 2011 to study significant wave heights and found that the tide table of Guamaré (approximately 40 km east of the table of Macau) had averages of 2.34 m (in syzygy tides) and 2.21 m (in quadrature tides), both above the reduction level.…”
Section: Tidal Behaviour and Return Periodmentioning
confidence: 99%